2021
DOI: 10.3892/mmr.2021.12316
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 6: Therapeutic prospects for tumours, and mechanisms of expression and regulation (Review)

Abstract: Tight junctions (TJs) are an important component of cell connectivity; they maintain cell polarity, permeability and adhesion, and participate in the regulation of cell proliferation and differentiation. The claudin (cldn) family is integral to TJs, and cldn6 is an important member of this family. abnormal expression of cldn6 can destroy the integrity of TJs through various mechanisms and can serve multiple roles in the occurrence and development of tumours. cldn6 is widely expressed in various tumours but rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…More than a simple static component that establishes the tight junction, CLDN6 is also a cellular signaling component that functions to receive environmental signals and transmit them intracellularly. It is relevant to multiple biological behaviors of tumors such as proliferation, apoptosis, autophagy, drug resistance, and metastasis [ 7 , 23 ]. CLDN6 is an ideal target for antibody approaches of high potency in cancers with high CLDN6 expression based on the fact that CLDN6 is undetectable in the adult tissues [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than a simple static component that establishes the tight junction, CLDN6 is also a cellular signaling component that functions to receive environmental signals and transmit them intracellularly. It is relevant to multiple biological behaviors of tumors such as proliferation, apoptosis, autophagy, drug resistance, and metastasis [ 7 , 23 ]. CLDN6 is an ideal target for antibody approaches of high potency in cancers with high CLDN6 expression based on the fact that CLDN6 is undetectable in the adult tissues [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of CLDNs, CLDN6 is involved in regulating epidermal barrier formation [ 3 , 4 , 5 ] and epithelial permeability [ 6 ]. In addition to the above canonical functions, dysregulated CLDN6 is related to neoplastic growth and aggressiveness in cancers [ 7 ]. We have reported that CLDN6 overexpression suppressed breast cancer metastasis by inhibiting EMT [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CLDN-3 and CLDN-4 is observed in EEC and may be involved in endometrial tumorgenesis [ 23 , 24 ]. CLDN-6 has potential as a carcinoembryonic antigen, is highly expressed in EEC, and promotes endometrial cancer progression [ 25 , 26 , 27 ].…”
Section: Tight Junction Proteins In Endometriosis and Endometrial Cancermentioning
confidence: 99%
“…The tight junctions (TJs) between the intestinal epithelial cells (IECs) constitute the second barrier of the intestinal barrier ( 9 , 10 ), which are the determinant of the intestinal barrier function ( 5 ). The TJs’ structure is composed of transmembrane proteins such as claudin, occludin, tricellulin, and junction adhesion molecules ( 11 , 12 ). TJs connect IECs to form a continuous polarized single-layer structure, separating the lumen from the lamina propria ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%